Priapism as the initial manifestation of chronic myeloid leukemia, a rare presentation - Miguel-Ibañez, Regina de; Sanchez-Gonzalez, Marcos Daniel; Herrera-Madrid, Diana Arlett (International Journal of Research in Medical Sciences, 2021)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm with a median age of diagnosis in Mexico of 40 years. The initial manifestations are varied; however, priapism is a very rare entity associated to CML. We report the case of an 18-year-old male with an 8-hour episode of ischemic priapism managed with cavernous lavage, achieving complete flaccidity of the penis. The patient was diagnosed with CML, initiating cytoreduction with hydroxycarbamide and after having molecular confirmation, we started treatment with a tyrosine kinase inhibitor. The patient was discharged in excellent conditions, without sequelae of erectile dysfunction, all this attributed to the time of evolution, the adequate management of the urological emergency and the prompt identification and treatment of the precipitating condition.